2014
DOI: 10.1378/chest.13-1176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coexisting COPD on Survival of Patients With Early-Stage Non-small Cell Lung Cancer Undergoing Surgical Resection

Abstract: Background: COPD is a recognized risk factor for lung cancer, but studies of coexisting COPD in relation to lung cancer outcomes are limited. We assessed the impact of COPD on overall survival (OS) and progression-free survival (PFS) in patients with early-stage non-small cell lung cancer (NSCLC). Abbreviations: HR 5 hazard ratio; HRadj 5 adjusted hazard ratio; MGH 5 Massachusetts General Hospital; NSCLC 5 non-small cell lung cancer; OS 5 overall survival; PFS 5 progression-free survival; SCC 5 squamous cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 43 publications
13
115
2
1
Order By: Relevance
“…Severe COPD was not associated with increased 1-year mortality, but after 2 and 5 years, these patients had increased mortality compared to patients with normal lung function and mild to moderate COPD. These results demonstrating the long-term mortality of patients with severe COPD are in accordance with comparable studies [59,60]. In addition, the coinciding results supports the external validity and generalizability of our study.…”
Section: Discussion Of Main Resultssupporting
confidence: 92%
“…Severe COPD was not associated with increased 1-year mortality, but after 2 and 5 years, these patients had increased mortality compared to patients with normal lung function and mild to moderate COPD. These results demonstrating the long-term mortality of patients with severe COPD are in accordance with comparable studies [59,60]. In addition, the coinciding results supports the external validity and generalizability of our study.…”
Section: Discussion Of Main Resultssupporting
confidence: 92%
“…Severe COPD increases the risk of postoperative complications and reduces the extent of the lung that can be safely resected [21,22,23]. In studies focusing on resected patients with early NSCLC, coexisting COPD was associated with poorer survival outcome in comparison to those without COPD [23,24]. In addition, it is well known that the prevalence rates of lung cancer and COPD increase with age [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Sekine et al reported an increased rate of postoperative complications, including pneumonia and the need for a tracheostomy, increased cancer recurrence, and a decreased 5-year survival rate in patients with completely resected stage IA nonsmall cell lung cancer (NSCLC) and coexisting COPD; the 5-year survival rates of patients with COPD (n = 80) and of those without COPD (n = 362) were 77.0% and 91.6%, respectively (P = 0.0001) [52] . A recent retrospective study involving 902 patients with stage IA to IIB NSCLC treated with surgical resection also disclosed that 63.4% (572/902) of the patient population had self-reported, physician-diagnosed COPD, and the patients with COPD had a poorer 5-year progression-free survival rate (50.1% vs 60.6%, P = 0.007) and a poorer 5-year overall survival rate (54.4% vs 69.0%, P = 0.0002) than the patients without COPD [53] .…”
Section: Prognosismentioning
confidence: 96%